The effectiveness of crisis communication strategies in public relations: A comparative study of traditional and digital approaches - Binlibdah, Saud (Edelweiss Applied Science and Technology, 2025)
This research examines the effectiveness of traditional and digital communication strategies in crisis management, with a particular emphasis on integrating both approaches to enhance organizational crisis responses. It explores key theoretical frameworks for understanding crises and communication strategies, addressing a critical knowledge gap in the existing literature. Previous studies have primarily examined traditional and digital strategies in isolation, lacking a holistic perspective on their integration. Using a mixed-methods approach, this study incorporates quantitative data from surveys of 300 participants and qualitative insights from interviews with 30 experts. The findings indicate that traditional tools, such as press releases and media conferences, enhance credibility and message consistency but are limited in flexibility and response speed. Conversely, digital tools, including social media platforms, enable rapid responses and broad audience reach but face challenges like rumor proliferation and content management difficulties. The study proposes an integrative model that combines the reliability of traditional tools with the speed and interactivity of digital platforms. This model is tailored to the specific nature of crises and the characteristics of target audiences. Additionally, practical recommendations address technical challenges, such as utilizing artificial intelligence for data analysis and rumor management, and improving stakeholder coordination through centralized, technology-driven platforms. This research bridges a significant knowledge gap by offering a comparative analysis, real-world case studies, and strategic recommendations. It contributes both scientifically and practically to the field of crisis management, advancing the effectiveness of corporate communication strategies and laying the foundation for developing comprehensive, adaptive solutions to modern challenges.